Energy Sources Diversification Towards Achieving Energy Independence - Karlibaeva, Raya; Matkarimov, Feruz; Isaev, Fakhriddin; Tursunov, Olim; Rajabova, Nilufar; Atabayeva, Karomat (International Journal of Energy Economics and Policy, 2025)
This study, for the 1st time, reviews the cause of energy sources diversification on energy independence risk. To achieve this objective, the dataset across 64 countries spanning the time in the middle of 2000 and 2018 is used. For empirical analysis, method of moments quantile regression (MMQR) to cope with heteroscedasticity, partially linear functional-coefficient (PLFC) model to run nonlinear analysis, also difference-in-differences (DID) method to deal with endogeneity of Chinese energy investment are employed. The MMQR findings show that energy sources diversification has an adverse cause to energy independence risk across all the quantiles, 10-90%, and the development stage of the nations. Moreover, PLFC estimations also reveal that nonlinear relation is significant and depends on stage of economic development. Further, our findings obtained by DID method represent that Chinese energy investment is beneficial to cope with energy independence risk.